The dynamics of comparison operation in construction in mentally retarded children - Karvelis, V. (Psichologija, 1966)
Many soviet psychologists studied comparison processes in mentally retarded children, but this field remains little explored in terms of the working constructional activity of mentally retarded children. The analysis of the handicraft lessons for mentally retarded children and our experimental constructional tasks showed that in practical activities while performing constructional tasks children encounter the necessity to compare work materials according to their features as well as compare own work with an example in order to evaluate the quality of own product.We performed an experiment with the students of 1st-3rd assisted grade. The children needed to compare own product with an example while performing the task.The first and the second activity series included the same task: to assemble an object from given parts according to given example. Other experimental activities were also performed during which the children were taught how to perform a comparison. The essence of the experiment was that the student did not receive an imposed solution to a mental task. If the student encountered difficulties in performing the task, it was explained and the student received an advised solution.After the teaching experiment the children began to reproduce the examples better in their products. The similarity between example and product increased significantly and the students could qualitatively compare own products with an example. Teaching of comparison in the process of constructional activity creates the grounds for further skills development of assisted school students.
Keywords: mental retardation; thinking; thought operations; comparison